Rekomendasi Skema Sistem Satu Data Daerah - Hasudungan, Rocky Gunung; Galistya, Theresia Mutiara; Solana, Aryadi; Aini, Nur; Ngurah Diksa, I Gusti Bagus; Sri Jayanti, Dewa Ayu (Politeknik Statistika STIS, 2024)
Indonesia has launched a National Statistics System (SSN) and the One Data Indonesia (SDI) program to ensure standardized and interoperable sectoral statistical data. Jembrana Regency, through the innovation